SENI DAN SOSIALISME DALAM PEMIKIRAN LEON TROTSKY - Umar, Fauzi (Saskara : Indonesian Journal of Society Studies, 2021)
Art is often discussed in the sphere of socialism. art becomes a medium of socialism to show differences in thinking from capitalism. Trotsky as one of the influential socialist figures in the October Revolution has a different view of the concept of art. According to Trotsky, art must be free from political influence in order for artists to have freedom of thought, although the state must have a special department to manage art. Apart from art, a clear difference between Trotsky and the Soviet Union's socialist thinkers was socialism. Trotsky's concept of socialism aimed at establishing the Fourth International. In a sense, Trotsky's concept of socialism has a wider scope and this is the basis for the difference between Trotsky's and Stalin's thinking. Therefore, this paper will discuss Trotsky's thoughts on the concept of art and socialism.